Perspectives on the popularization of smart senior care to meet the demands of older adults living alone in communities of Southwest China: A qualitative study - Kong, Dehui; Liu, Siqi; Hong, Yan; Chen, Kun; Luo, Yu (Frontiers in Public Health, 2023)
Background: Older adults who live alone generally face challenges in daily life and maintaining health. Currently, however, their growing demands cannot be satisfied with high quality, which may be settled in a smart manner. Hence, the improvement of smart senior care may produce more positive meanings in promoting health and sense of happiness of this population. This study aims to explore the perceptions of demands and satisfaction regarding eldercare services of the community-dwelling elderly who live alone in Southwest China, thus providing reference for the popularization of smart senior care. Methods: This study adopted a qualitative approach. Semi-structured, in-depth individual interviews were conducted with 15 community-dwelling older adults living alone between March to May 2021. Thematic analysis was applied to analyze the data. Results: Through data analysis, three major themes and subcategories were generated: “necessities” (contradiction: more meticulous daily life care and higher psychological needs versus the current lower satisfaction status quo; conflict: higher demands for medical and emergency care against less access at present), “feasibilities” (objectively feasible: the popularization of smart devices and applications; subjectively feasible: interests in obtaining health information) and “existing obstacles” (insufficient publicity; technophobia; patterned living habits; concerns). Conclusions: Smart senior care may resolve the contradiction between the shortage of medical resources and increasing demands for elderly care. Despite several obstacles that stand in the way of the popularization of smart senior care, the necessities and feasibilities provide preliminary foundation for its development and popularization. Decision-makers, communities, developers and providers should cooperate to make smart eldercare more known and available to seniors living alone, facilitating independence and ageing in place, promoting healthy ageing.